Effect of incorporating alum in cane juice clarification efficiency and sucrose losses - Benard M. Kimatu; Abdul K. Faraj; Symon M. Mahungu (International Journal of Food Studies, 2015)
The effect of incorporating alum in the clarification stage of raw juice in sugarcane processing on the juice quality and sucrose loss was investigated. Alum was incorporated in both intermediate and hot liming clarification processes of cane juicing. One portion of the cane juice was used for With Pretreatment Treatment (WPT) while the other portion constituted No Pre-treatment (NPT) juice. Alum at levels of 0 mg L−1 , 50 mg L−1 , 100 mg L−1 and 150 mg L−1 was incorporated in both intermediate and hot liming clarification processes in each of the two cane juice portions. Sugar concentration (sucrose, glucose and fructose), ◦Brix, pH, colour, settling performance (initial settling rates (ISR), final mud volume (MV∞), and turbidity) and residual aluminium ion concentration were evaluated. Any significant variations (p < 0.05) in these parameters were assessed. The study found significantly lower (p < 0.05) sucrose losses in clarified juice from intermediate liming of WPT after alum treatment than in the rest of the clarified juices. Colour and turbidity in the pre-treated cane juice of intermediate liming was reduced by 36.9% and 98.1%, respectively at 150 mg L−1 alum level. An initial settling rate of 260 ml min−1 in WPT cane juice of intermediate liming at 150 mg L−1 alum level resulted in the most compact final mud volume of 10.3%. The residual aluminium concentration (0.025 to 0.048 mg L−1 ) in alum treated clarified juices was lower than the natural aluminium concentration (0.088 mg L−1 ) in untreated cane juice. This study showed the potential for the use of alum in cane juice clarification to improve on clarification efficiency and lower sucrose loss.